2014
DOI: 10.1088/0741-3335/56/2/025004
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of a mini-magnetosphere

Abstract: Magnetosphere at ion kinetic scales, or mini-magnetosphere, possesses unusual features as predicted by numerical simulations. However, there are practically no data on the subject from space observations and the data which are available are far too incomplete. In the present work we describe results of laboratory experiment on interaction of plasma flow with magnetic dipole with parameters such that ion inertial length is smaller than a size of observed magnetosphere. A detailed structure of non-coplanar or ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The two regions of strongest magnetic field are co-located with the brightest albedo markings. As the solar wind interaction with magnetic dipoles has been well studied [17][18][19][20][21][22][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] , it allows us better insight to confidently disentangle the plasma interaction with Reiner Gamma's magnetic topology. The high proton density profile surrounding the density cavities ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The two regions of strongest magnetic field are co-located with the brightest albedo markings. As the solar wind interaction with magnetic dipoles has been well studied [17][18][19][20][21][22][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] , it allows us better insight to confidently disentangle the plasma interaction with Reiner Gamma's magnetic topology. The high proton density profile surrounding the density cavities ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Wang et al [2012Wang et al [ , 2013 identified potential structures related to the surface charging in a laboratory study using a magnetic dipole and a plasma flow with unmagnetized protons and magnetized electrons. Shaikhislamov et al [2013Shaikhislamov et al [ , 2014 studied laboratory measurements and a Hall-MHD simulation arguing that the Hall term of the electric field may play an important role in decoupling the ion and electron flow in lunar minimagnetospheres. Self-consistent fluid simulations predict the formation of lunar minimagnetospheres around the strongest lunar magnetic anomalies [e.g., Harnett and Winglee, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, the evolution from magnetohydrodynamic [ Harnett and Winglee , ; Shaikhislamov et al , , ; Xie et al , ] and hybrid [ Kallio et al , ; Jarvinen et al , ; Fatemi et al , ] toward full‐kinetic simulations [ Deca et al , , ; Ashida et al , ] has made it abundantly clear that the solar wind‐LMA interaction is highly nonadiabatic. The ability to investigate finite gyroradius effects and charge separation is therefore an absolute must to correctly describe the electron physics‐dominated LMA environment.…”
Section: Introductionmentioning
confidence: 99%